An Improved Hybrid Index Structrue for Per-Calculated Downwash Flow Field Visualization. Issue 4 (August 2020) - Ni, Ming; Wang, Hongjie; Li, Xingcheng; Liao, Yilin; Fu, Lin
Abstract: With the application of aerial plant protection technology in field spraying, how to intuitively and quickly obtain the impact of propeller downwash flow field on droplet deposition has become an important aspect of field management. The unstructured grid is used for the propeller rotation area, the structured grid is used for the surrounding fluid domain; After the mesh generation, use Fluent software to iteratively calculate the propeller-fluid domain mesh model until the calculated residual values converge, In this way, the aerodynamic parameters of the propeller and the discrete grid value distribution of the surrounding fluid domain are obtained; In the OpenGL environment, use SPH method to establish the physical attribute particle model of the droplet, Create a mixed space domain of octree and KD tree at the same time, import pre-calculated grid numerical distribution data, and initialize the octree and KD tree in the fluid domain; Finally, the hybrid structure index algorithm is used to obtain the changes of the flow field around the particles, and the motion is solved based on Newton's law to obtain the multi-particle flow field motion trajectory with high frame rate.